Single Atom Engineering for Nanorobotics - Ju, Xiaohui; Pumera, Martin (ACS nano, 2024)
The fields of single atom engineering represent cutting-edge areas in nanotechnology and materials science, pushing the boundaries of how small we can go in engineering functional devices and materials. Nanorobots, or nanobots, are robotic systems scaled down to the nanometer level and designed to perform tasks at similarly small scales. Single atom engineering, on the other hand, involves manipulating individual atoms to create precise materials and devices with controlled properties and functionalities. By integrating single atom engineering into nanorobotics, we unlock the potential to enable the precise incorporation of multiple functionalities onto these minuscule machines with nanometer-level precision. In this perspective, we describe the nascent field of single atom engineering in nanorobotics.
Keywords: nanorobotics; single-atom engineering; materials science